2016
DOI: 10.5851/kosfa.2016.36.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Foodborne Pathogens and Mycotoxins in Eggs and Chicken Feeds from Farms to Retail Markets

Abstract: Contamination by foodborne pathogens and mycotoxins was examined in 475 eggs and 20 feed samples collected from three egg layer farms, three egg-processing units, and five retail markets in Korea. Microbial contamination with Salmonella species, Escherichia coli, and Arcobacter species was examined by bacterial culture and multiplex polymerase chain reaction (PCR). The contamination levels of aflatoxins, ochratoxins, and zearalenone in eggs and chicken feeds were simultaneously analyzed with high-performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
1
12
0
1
Order By: Relevance
“…Many authors reported that Salmonella failed to be detected which agreed with findings of this study as (El-Leboudy et al, 2011,Ghasemian Safaei et al, 2011, Mahdavi et al, 2012, El-Kholy et al, 2014, Abdel-Latif and Saad, 2015, Lee et al, 2016. Higher percentages of Salmonella were illustrated by (Adesiyun et al, 2005, Evêncio-Luz et al, 2012, Ghazi and Amer, 2015, Amin, 2017, Awny et al, 2018, Al Momani et al, 2018.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Many authors reported that Salmonella failed to be detected which agreed with findings of this study as (El-Leboudy et al, 2011,Ghasemian Safaei et al, 2011, Mahdavi et al, 2012, El-Kholy et al, 2014, Abdel-Latif and Saad, 2015, Lee et al, 2016. Higher percentages of Salmonella were illustrated by (Adesiyun et al, 2005, Evêncio-Luz et al, 2012, Ghazi and Amer, 2015, Amin, 2017, Awny et al, 2018, Al Momani et al, 2018.…”
Section: Discussionsupporting
confidence: 86%
“…Higher percentages of Salmonella were illustrated by (Adesiyun et al, 2005, Evêncio-Luz et al, 2012, Ghazi and Amer, 2015, Amin, 2017, Awny et al, 2018, Al Momani et al, 2018. Failure to detect fecal E. coli in our results agreed with (Bahobail et al, 2012, Siriporn et al, 2015., while True fecal E. coli were shown with high incidence rate in the results of (Adesiyun et al, 2005, El-Kholy et al, 2014, Eid et al, 2015, Mansour et al, 2015, Elafify et al, 2016, Lee et al, 2016, Momani et al, 2018.…”
Section: Discussionmentioning
confidence: 97%
“…A search of the literature in PubMed, including the search terms "Mycotoxin AND feed AND fluorescence," limited to the last 10 years, revealed a total of 20 studies on the analysis of mycotoxins in feed (no raw materials) using LC-FLD [4,5,9,16,17,30,[32][33][34][39][40][41][42][43][44][45][46][47][48][49]. AFs are the most widely studied mycotoxins [4,5,9,16,17,30,[40][41][42][43], particularly AFB1, as a single mycotoxin [44,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum concentrations reach for aflatoxin are 22.39 (AFB 2 ) and 21.84 (AFG 2 ) μg kg − 1 (Table 4). Animal feed contaminated with mycotoxins can negatively impact health, productiveness and general well-being of the animal additionally, carry-over to other food matrices [e.g., milk (Fink-Gremmels 2008) and eggs (Lee et al 2016)] is a real concern. Of special concern is aflatoxin prevalence in feeds as they are recognized as cytotoxic, teratogenic, and immunotoxic (Granados-Chinchilla et al 2017).…”
Section: Antimicrobial Analysismentioning
confidence: 99%